(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Due to technological developments in the Iraqi banking sector, which is the use of electronic payment systems within the banking infrastructure. This has led to speed and accuracy in the completion of transactions, reduced costs, increased revenues and efficiency. This research examines the challenges and risks facing the Iraqi banking sector as a result of its use of electronic payment systems. And show its impact on the profitability of commercial banks. The research was based on the main hypothesis that there is a statistically significant moral impact relationship between electronic payment systems and the profitability of banks. Iraqi commercial banks were chosen as a research community, All Iraqi commercial banks that participate in each of the immediate Real Time Gross settlement system (RTGS), the Automated clearing House system (ACH) and the retail payment system infrastructure (RPSI) have been listed. Based on data obtained from the Central Bank of Iraq and some banks, the research sample was identified, which includes AL-Rafidain Bank, National Bank of Iraq, Ashur International Bank and The International Development Bank. From the statistical analysis of the research variables, the results of the analysis and measurement showed a statistically significant moral effect relationship between electronic payment systems and the profitability of commercial banks sample research. The more commercial banks use electronic payment systems to complete their transactions, the profitability of these banks has increased. The research recommended the need to increase investment by banks on the infrastructure of electronic payment systems, as they should be reliable, cost-effective and accessible from the majority of the community, which positively affects profitability.